1993
DOI: 10.1073/pnas.90.21.9813
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide protects against cellular damage and cytotoxicity from reactive oxygen species.

Abstract: Nitric oxide, NO, which is generated by various components of the immune system, has been presumed to be cytotoxic. However, NO has been proposed to be protective against cellular damage resulting during ischemia reperfusion. Along with NO there is often concomitant formation of superoxide/hydrogen peroxide, and hence a synergistic relationship between the cytotoxic effects of nitric oxide and these active oxygen species is frequently assumed. To study more peroxide or to hypoxanthine/xanthine oxidase result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
346
0
12

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(385 citation statements)
references
References 36 publications
22
346
0
12
Order By: Relevance
“…2001; Wink et al, 1993). Accordingly, we showed that NO supplementation to hyperglycemic media reduces hyperglycemia-induced ROS.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…2001; Wink et al, 1993). Accordingly, we showed that NO supplementation to hyperglycemic media reduces hyperglycemia-induced ROS.…”
Section: Discussionmentioning
confidence: 83%
“…Studies using low doses of NO donors demonstrated that NO directly acts as an antioxidant (Chang et al, 1996;Joshi et al, 1999;Kim et al, 1995;Wink et al, 1993). Therefore, we hypothesized that the vasculopathy induced by L-NMMA may be due to increased ROS, suggesting a common pathway with hyperglycemia.…”
Section: No Depletion Increases Ros Production: a Common Pathway In Vmentioning
confidence: 96%
“…The former effect is attributed to the formation of the toxic peroxynitrite after reaction with O 2 ÏȘ [11]. The latter effect is not well defined, although inhibition of oxidative killing of Chinese hamster V79 cells [27], attenuation of low-density lipoprotein oxidation [28], and prevention of myocardial ischemiareperfusion injury [10] have been demonstrated. Our goal was to understand the interactive role of NO and ROI in cellular events that culminate in PMN-mediated EC injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that NO at lower non-toxic levels may also function as a cytoprotective and antioxidant agent in different models of oxidative stress. Thus, Wink and co-workers [3] reported NO to prevent cellular damage induced by hydrogen peroxide in lung fibroblasts. Similar results were published by Motterlini et al [4] who found that pretreatment with NO donors rendered the vascular endothelium more resistant against the toxic effects of oxygen-free radicals, i.e.…”
Section: Introductionmentioning
confidence: 98%